Wildlife roadkills in the Colombian Andes: Hotspots, causes, and most affected species - Angarita-Corzo, Karime; Ceballos, Claudia P; Rojano-Bolaño, Cesar; Correa-Valencia, Nathalia M (Revista Colombiana de Ciencias Pecuarias, 2024)
Background: Despite the improvements in connectivity and mobility of the national highways, road infrastructure promotes significant environmental disturbances, including wildlife-vehicles collisions. Objective: To estimate the direct road mortality of wildlife species during the two-lane Autopista al Mar 1 highway construction, Antioquia (Colombia), 2018-2021. Methods: A retrospective observational study was conducted, using primary sources of information. Descriptive statistics were used to estimate the direct road mortality for each taxonomic group, and two roadkill rates were calculated (Roadkills/day and Roadkills/km/day). Events and month/year relations were explored using ANOVA, critical points were identified using a conglomerates analysis and Ripley's K statistic, and a logistic regression was performed to determine which environmental parameters best-predicted wildlife roadkill along the road. Results: A total of 295 events were recorded, being Didelphis marsupialis (18.3%) and Iguana iguana (13.6%) the most frequent roadkilled species in the study area. The number of roadkills/day was 0.7553 and the number of roadkills/km/day was 0.0218; at least 275.68 individuals are road killed every year in this highway. A greater value of spatial aggregation was found in eight critical points of the highway but were not associated to any of the environmental parameters explored. Conclusion: Opossums and iguanas represented more than a third of the animal mortality recorded on the road of interest. Environmental and temporal factors did not explain this mortality, but explanatory factors associated with the COVID-19 pandemic are hypothesized. The road mortality data presented can serve the management of road accidents, mainly the implementation of mitigation measures that can reduce the mortality of wildlife species on the road.